2013
DOI: 10.1038/nmat3596
|View full text |Cite
|
Sign up to set email alerts
|

Surface chemistry mediates thermal transport in three-dimensional nanocrystal arrays

Abstract: Arrays of ligand-stabilized colloidal nanocrystals with sizetunable electronic structure are promising alternatives to single-crystal semiconductors in electronic, optoelectronic and energy-related applications 1-5 . Hard/soft interfaces in these nanocrystal arrays (NCAs) create a complex and uncharted vibrational landscape for thermal energy transport that will influence their technological feasibility. Here, we present thermal conductivity measurements of NCAs (CdSe, PbS, PbSe, PbTe, Fe 3 O 4 and Au) and rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

32
241
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 228 publications
(273 citation statements)
references
References 31 publications
32
241
0
Order By: Relevance
“…On the other hand, when the diameter is much bigger than the Kapitza length, α tends to zero, and eq 2 simplifies to an EMA formulation that has no dependence on the interfacial thermal conductance. 36 In our previous study, 24 the experimentally measured thermal conductivities of PbS NCAs with diameters greater than 3.5 nm agree with the predictions of eq 2 when the interfacial thermal conductance between the core and ligands is used as a fitting parameter. We now use this EMA-h model to interpret our simulation predictions.…”
Section: ■ Results and Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…On the other hand, when the diameter is much bigger than the Kapitza length, α tends to zero, and eq 2 simplifies to an EMA formulation that has no dependence on the interfacial thermal conductance. 36 In our previous study, 24 the experimentally measured thermal conductivities of PbS NCAs with diameters greater than 3.5 nm agree with the predictions of eq 2 when the interfacial thermal conductance between the core and ligands is used as a fitting parameter. We now use this EMA-h model to interpret our simulation predictions.…”
Section: ■ Results and Discussionsupporting
confidence: 71%
“…The data agree with the geometry-based analytical model of Jimenez et al 56 Figure 2. Predicted thermal conductivities and corresponding experimental measurements 24 of varying the NCA thickness. Figure 3.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been recently shown that thermal conductivity of QD layers can be orders of magnitude lower than that of traditional semiconductors. 48 The optimization of thermal management in QLEDs offers a promising direction toward improved stability, effi ciency, and brightness. One should also look beyond using organic molecules as surface ligands for QDs-inorganic and hybrid ligands for colloidal NCs could provide an interparticle medium that is more thermally conductive and/or transparent for charge carriers.…”
Section: Discussionmentioning
confidence: 99%